In-vitro reactions of lymphocytes in rheumatoid arthritis and other rheumatic diseases. Issue 6 (December 1979) - Froebel, K; Sturrock, R D; Reynolds, P; Grennan, A; Roxburgh, A; MacSween, R N
Abstract : Various lymphocyte functions and the percentage of different subpopulations have been measured in groups of patients with seropositive rheumatoid arthritis, seronegative ankylosing spondylitis, and psoriatic arthritis, Sjögren's syndrome, sicca complex, and in normal controls. Several abnormal results were found–in the responses to mitogens, in the antibody-dependent cytotoxic test, and in the percentages of EA rosettes (antibody sensitised chick red cells test) and surface immunoglobulin-bearing cells. In the light of these findings cytotoxicity and lymphocyte subpopulations were measured in further groups of rheumatoid arthritis patients in whom the disease was at different stages. The results showed that the changes in cytotoxic potential occurred in patients with active arthritis. Correlation tests showed significant positive associations between the percentage of SE rosette-forming cells (sheep red cells test) and the mitogenic responses to phytohaemagglutinin and concanavalin A, and between the percentage of EA rosette-forming cells and the levels of antibody-dependent cytotoxicity. The results are discussed in the light of our understanding of cellular subpopulations in the immune system.